2013
DOI: 10.1086/bblv225n3p161
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Responses of Cuttlefish to Different Teleost Predators

Abstract: Abstract. We evaluated cuttlefish (Sepia officinalis) responses to three teleost predators: bluefish (Pomatomus saltatrix), summer flounder (Paralichthys dentatus), and black seabass (Centropristis striata). We hypothesized that the distinct body shapes, swimming behaviors, and predation tactics exhibited by the three fishes would elicit markedly different antipredator responses by cuttlefish. Over the course of 25 predator-prey behavioral trials, 3 primary and 15 secondary defense behaviors of cuttlefish were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 65 publications
0
34
1
Order By: Relevance
“…One of the possible functions of "all dark" is masquerade, that is, S. pharaonis may mimic inedible objects such as a clump of seaweeds (see Buresch et al, 2011). Alternatively, "all dark" may function as a secondary defense, as several previous studies have suggested for S. officinalis (e.g., Adamo et al, 2006;Langridge, 2009;Staudinger et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…One of the possible functions of "all dark" is masquerade, that is, S. pharaonis may mimic inedible objects such as a clump of seaweeds (see Buresch et al, 2011). Alternatively, "all dark" may function as a secondary defense, as several previous studies have suggested for S. officinalis (e.g., Adamo et al, 2006;Langridge, 2009;Staudinger et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…As we predicted, the results indicated that cuttlefish changed its body pattern according to PPD, and also indicated that the trajectory of the approaching model affected the body pattern of cuttlefish even when the linear PPD was the same. "Eyespots", which is assumed to function as secondary defense (Langridge, 2009;Staudinger et al, 2013), was expressed only in the situation expected to have high predation risk, that is, when linear PPD was short in T2. On the other hand, "uniform light", "disruptive" and "center circle", which are supposed to function as camouflage, tended to be used in the situations expected to be low predation risk, that is, before the model was presented and when PPD was long.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations